Contribution of Islamic Boarding Schools to Community Economic Development - Agnes Cahyatria Manaku (Create: Journal of Islamic Management and Business, 2025)
Economic changes experienced by the community in Kembangbelor village Pacet District of Mojokerto Regency cannot be separated from the role of Amanatul Ummah Islamic Boarding School. Previously the level of poverty in the village was still high because many of the people worked as farmers. The existence of cottages helped improve the economy of the community. The role in this case is a device of behavior expected and owned by people or institutions domiciled in the community. The research aims to analyze the role given by Amanatul Ummah Islamic Boarding School to the economy of Kembangbelor village community. The study used qualitative research types and case study approaches. The research location was in Kembangbelor village, Pacet District, Mojokerto Regency. The data collection techniques used were secondary data and primary data, while data analysis techniques used were from Miles and Hiberman. The results showed the role of Amanatul Ummah Islamic Boarding School on the community economy, including creating jobs by inviting people to contribute by providing their services as the security guards, cooks, canteen officers, janitors, building porters and laundry workers. Another role is to open business opportunities for the community, such us teachers, outlets, coffee shops, street vendors, inns and even parking attendants. Based on this role, the Amanatul Ummah Islamic Boarding School indirectly empowers the community in improving the economy, but a wider community empowerment program is needed to improve the ability and independence of the community